Laminate
Patent Information
- Application Number
- JP2023201621
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-11-29
- Publication Date
- 2025-02-20
Smart Images

Figure 2025024657000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive composition, a method for producing a laminate, and a laminate. [Background technology]
[0002] Conventionally, in order to dissipate heat generated by an LED (light emitting diode) chip or an IC (integrated circuit) chip mounted on a heat dissipation substrate to a heat sink via the heat dissipation substrate, the heat dissipation substrate and the heat sink have been bonded together with a thermally conductive composition.
[0003] In order for such a thermally conductive composition to have high thermal conductivity and low thermal resistance, a high loading of metal filler is necessary. In the case of a liquid composition, the fluidity is reduced, and if the composition is made into a sheet, the sheet becomes hard, losing its conformability and increasing the interfacial resistance.
[0004] In order to solve the above problems, for example, a thermally conductive adhesive has been proposed that has a thermosetting adhesive containing a curing component and a curing agent, and a metal filler dispersed in the thermosetting adhesive, in which the metal filler has silver powder and solder powder, and the solder powder has a melting temperature lower than the thermosetting treatment temperature of the thermally conductive adhesive and reacts with the silver powder under the thermosetting treatment conditions of the thermosetting adhesive to produce a high-melting point solder alloy that has a melting point higher than the melting temperature of the solder powder, and the curing agent is a curing agent that has flux activity against the metal filler, the curing component is a glycidyl ether type epoxy resin, and the curing agent is a monoanhydride of a tricarboxylic acid (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5796242 Summary of the Invention [Problem to be solved by the invention]
[0006] However, in the conventional technology described in the above Patent Document 1, when a network of a high-melting-point solder alloy is formed by bonding silver particles with a small average particle size using solder powder with a large average particle size, the content of the solder powder with low thermal conductivity by volume becomes greater than the content of the silver particles, and high thermal conductivity and low thermal resistance cannot be achieved. In addition, when solder powder with a low melting point is used, there is a problem that a resin layer is formed on the surface of the interface material that is difficult for the molten solder powder to wet, resulting in a decrease in thermal conductivity.
[0007] The present invention aims to solve the above-mentioned problems in the prior art and to achieve the following object: That is, the present invention aims to provide a thermally conductive composition that can realize high thermal conductivity and low thermal resistance. [Means for solving the problem]
[0008] The means for solving the above problems are as follows. <1> Contains a curing component, a curing agent, and a metal filler; The metal filler is at least one selected from silver particles, copper particles, silver-coated copper particles, and copper-coated silver particles, The volume filling rate of particles having a particle diameter of 1 μm or less in the metal filler is 5 vol % or more, The thermally conductive composition is characterized in that the volumetric filling rate of the metal filler is 30 volume % or more and 90 volume % or less. <2> The volumetric filling rate of the metal filler is 50% by volume or more and 80% by volume or less. <1> The thermally conductive composition according to claim 1, <3> The volume filling rate of the metal filler particles having a particle diameter of 1 μm or less is 8 volume % or more. <1> from <2> The thermally conductive composition according to any one of claims 1 to 5, <4> The curing component is at least one of an oxirane ring compound and an oxetane compound. <1> from <3> The thermally conductive composition according to any one of claims 1 to 5, <5> the curing component is an oxirane ring compound, The curing agent is an imidazole-based curing agent. <1> from <4> The thermally conductive composition according to any one of claims 1 to 5, <6> The above-mentioned polymer further contains, in its molecule, at least one structure selected from a phenoxy structure, a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, a polyamide structure, and a polycarbonate structure. <1> from <5> The thermally conductive composition according to any one of claims 1 to 5, <7> On the substrate, <1> from <6> applying the thermally conductive composition according to any one of the preceding claims; heating the thermally conductive composition; The method for producing a laminate is characterized by comprising the steps of: <8> applying a second thermally conductive composition onto the thermally conductive composition, the second thermally conductive composition including a second curing component, a second curing agent, a second metal filler, and low melting point metal particles; The step of heating is a step of heating the thermally conductive composition and the second thermally conductive composition. <7> 2. A method for producing the laminate according to claim 1 . <9> The substrate is a silicon substrate. <7> from <8> 13. A method for producing the laminate according to claim 12. <10> A substrate; A first thermally conductive layer is provided on the base material and contains a curing component, a curing agent, and a sintered body; the sintered body is formed by sintering at least one metal filler selected from silver particles, copper particles, silver-coated copper particles, and copper-coated silver particles, and is a sintered body that is continuous in a thickness direction and a planar direction of the first thermal conductive layer, The laminate is characterized in that the volume filling rate of the sintered body in the first thermally conductive layer is 30 volume % or more and 90 volume % or less. <11> The heat conductive layer further comprises a second heat conductive layer containing a second hardening component, a second hardening agent, a second metal filler, and low melting point metal particles. <10> 1. The laminate according to claim 1 . <12> The substrate is a silicon substrate. <10> from <11> The laminate according to any one of claims 1 to 5, <13> The thermal conductivity is 10 W / (m K) or more. <10> from <12> The laminate according to any one of claims 1 to 5, Effect of the Invention
[0009] According to the present invention, it is possible to provide a thermally conductive composition which can solve the above-mentioned problems in the prior art, achieve the above-mentioned objects, and realize high thermal conductivity and low thermal resistance. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic diagram showing an example of a process for producing a laminate according to the first embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing an example of the laminate according to the first embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing an example of a process of the method for producing a laminate according to the second embodiment. [Figure 4] FIG. 4 is a schematic diagram showing an example of a laminate according to the second embodiment. [Diagram 5] FIG. 5 is a schematic cross-sectional view showing an example of a heat dissipation structure having the laminate of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] (Thermal conductive composition) The thermally conductive composition of the present invention contains a curing component, a curing agent, and a metal filler, and further contains other components as required. The metal filler is at least one type selected from silver particles, copper particles, silver-coated copper particles, and copper-coated silver particles, the volume filling rate of particles having a particle size of 1 μm or less in the metal filler is 5 vol% or more, and the volume filling rate of the metal filler is 30 vol% or more and 90 vol% or less.
[0012] <Curing component> As the curing component, it is preferable to use at least one of an oxirane ring compound and an oxetane compound.
[0013] -Oxirane ring compounds- The oxirane ring compound is a compound having an oxirane ring, and examples thereof include epoxy resins. The epoxy resin is not particularly limited and can be appropriately selected depending on the purpose. Examples of the epoxy resin include glycidyl ether type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A type epoxy resins, trisphenol type epoxy resins, tetraphenol type epoxy resins, phenol-xylylene type epoxy resins, naphthol-xylylene type epoxy resins, phenol-naphthol type epoxy resins, phenol-dicyclopentadiene type epoxy resins, alicyclic epoxy resins, and aliphatic epoxy resins. These may be used alone or in combination of two or more.
[0014] -Oxetane compounds- The oxetane compound is a compound having an oxetanyl group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound. The oxetane compound may be a monofunctional oxetane compound having only one oxetanyl group, or a polyfunctional oxetane compound having two or more oxetanyl groups.
[0015] The oxetane compound is not particularly limited and can be appropriately selected depending on the purpose. Examples of the oxetane compound include 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, 1,4-bis(3-ethyl-3-oxetanylmeth- oxy)butane, 1,6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-(phenoxy)methyloxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, xylylene bisoxetane, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), isophthalic acid bis[(3-ethyl-3-oxetanyl)methyl]ester (OXIPA), and the like. These may be used alone or in combination of two or more.
[0016] As the oxetane compound, commercially available products can be used. Examples of the commercially available products include the "ARON OXETANE (registered trademark)" series sold by Toagosei Co., Ltd. and the "ETERNACOLL (registered trademark)" series sold by Ube Industries, Ltd.
[0017] Among the oxirane ring compounds and oxetane compounds, glycidyl ether type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, phenol-dicyclopentadiene type epoxy resins, bisphenol A type epoxy resins, aliphatic epoxy resins, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), and isophthalic acid bis[(3-ethyl-3-oxetanyl)methyl]ester (OXIPA) are preferred.
[0018] The content of the curing component is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5% by volume or more and 60% by volume or less based on the total amount of the thermally conductive composition.
[0019] <Hardening agent> The curing agent is a curing agent corresponding to the curing component, and examples thereof include polyaddition type curing agents such as polyfunctional carboxylic acid, acid anhydride type curing agent, aliphatic amine type curing agent, aromatic amine type curing agent (e.g., imidazole type curing agent), phenol type curing agent, and mercaptan type curing agent, and catalyst type curing agent such as imidazole. These may be used alone or in combination of two or more. Among these, aromatic amine-based curing agents are preferred, and imidazole-based curing agents are more preferred.
[0020] As the imidazole-based curing agent, commercially available products can be used, and examples of the commercially available products include 2P4MZ, 2PZ, and 2E4MZ-A of the "Curezol" series sold by Shikoku Chemical Industry Co., Ltd.; and HX-3941HP, HXA3922HP, HXA3792, HXA3932HP, HXA3042HP, HXA9322HP, HXA9382HP, HXA5052HP, and HXA3542HP of the "Novacure (registered trademark)" series sold by Asahi Chemical Industry Co., Ltd.
[0021] The acid anhydride-based curing agent is preferred in that, when the curing component is an epoxy resin, no gas is generated during thermal curing, a long pot life can be achieved when mixed with the epoxy resin, and a good balance can be achieved between the electrical properties, chemical properties, and mechanical properties of the resulting cured product. Examples of the acid anhydride curing agent include cyclohexane-1,2-dicarboxylic anhydride, monoacid anhydrides of tricarboxylic acids, etc. Examples of the monoacid anhydrides of tricarboxylic acids include cyclohexane-1,2,4-tricarboxylic-1,2-acid anhydride, etc.
[0022] The curing agent preferably has flux activity from the viewpoint of improving the wettability of the molten low-melting point metal particles to the thermally conductive particles. Examples of methods for making the curing agent exhibit flux activity include methods of introducing protonic acid groups such as carboxyl groups, sulfonyl groups, and phosphoric acid groups into the curing agent by known methods. Among these, it is preferable to introduce a carboxyl group from the viewpoint of reactivity with the epoxy resin or oxetane compound as the curing component, and examples thereof include polycarboxylic acids containing a carboxyl group such as glutaric acid and succinic acid. The curing agent may also be glutaric anhydride or a compound modified from succinic anhydride, or a metal salt of a polycarboxylic acid such as silver glutarate.
[0023] The content of the curing agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.1% by volume or more and 30% by volume or less based on the total amount of the thermally conductive composition.
[0024] In one embodiment, it is preferable that the curing component is an oxirane ring compound and the curing agent is an imidazole-based curing agent, since higher thermal conductivity can be achieved.
[0025] The molar equivalent ratio (A / B) between the curing component A and the curing agent B varies depending on the types of the curing component and the curing agent used and cannot be generally defined, but is preferably 5 or more and 15 or less, more preferably 7 or more and 13 or less, and even more preferably 9 or more and 11 or less. When the equivalent ratio (A / B) is 5 or more and 15 or less, when the thermally conductive composition is heated, a network of a sintered body can be formed by sintering the metal filler, and the sintered body having the network formed can be maintained with a high volume filling rate.
[0026] <Metal filler> The metal filler is at least one selected from silver particles, copper particles, silver-coated copper particles, and copper-coated silver particles. The volumetric filling rate of the metal filler particles having a particle size of 1 μm or less is 5% by volume or more, and the volumetric filling rate of the metal filler is 30% by volume or more and 90% by volume or less.
[0027] Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles. The shape of the metal filler is not particularly limited and may be appropriately selected depending on the purpose. Examples of the shape include spherical, flat, granular, and acicular shapes.
[0028] The volume average particle diameter (D 50 ) is preferably 1 μm or more and 10 μm or less, and more preferably 1 μm or more and 5 μm or less. When the volume average particle size of the metal filler is 1 μm or more and 10 μm or less, a network of a sintered body can be formed by sintering the metal filler when the thermally conductive composition is heated, and the thermally conductive composition can achieve high thermal conductivity and low thermal resistance. The volume average particle diameter (D 50 ) can be measured, for example, by a laser diffraction / scattering type particle size distribution measuring device (product name: Microtrac MT3300EXII).
[0029] The volumetric filling rate (c / C) of particles c having a particle size of 1 μm or less in the metal filler C is 5 volume % or more, and preferably 8 volume % or more. When the volume filling rate (c / C) of particles c having a particle size of 1 μm or less in the metal filler C is 5 volume % or more, a network of a sintered body can be formed by sintering the metal filler when the thermally conductive composition is heated, and the thermally conductive composition can have high thermal conductivity and low thermal resistance. The upper limit of the volume filling rate (c / C) of particles c having a particle size of 1 μm or less in the metal filler C is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 50 volume % or less, more preferably 40 volume % or less.
[0030] The volumetric filling rate of the metal filler is 30% by volume or more and 90% by volume or less, and preferably 50% by volume or more and 80% by volume or less. The lower limit of the volumetric filling rate of the metal filler is 30% by volume or more, preferably 50% by volume or more, more preferably 60% by volume or more, even more preferably 70% by volume or more, and particularly preferably 75% by volume or more. The upper limit of the volumetric filling rate of the metal filler is 90% by volume or less, preferably 85% by volume or less, and more preferably 80% by volume or less. When the volumetric filling rate of the metal filler is 30 volume % or more and 90 volume % or less, the thermal conductive composition can achieve high thermal conductivity and low thermal resistance.
[0031] <Specific polymer> The thermally conductive composition preferably contains a specific polymer in order to impart flexibility and sheetability. As the specific polymer, a polymer having at least one structure selected from a phenoxy structure, a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, a polyamide structure, and a polycarbonate structure in the molecule is used.
[0032] Examples of the specific polymer include a phenoxy structure such as bisphenol A type and bisphenol F type, a polybutadiene structure such as polybutadiene and hydrogenated polybutadiene, a polysiloxane structure such as silicone rubber, a poly(meth)acrylate structure, a polyalkylene structure (preferably a polyalkylene structure having 2 to 15 carbon atoms, more preferably a polyalkylene structure having 3 to 10 carbon atoms, and even more preferably a polyalkylene structure having 5 to 6 carbon atoms), a polyalkyleneoxy structure (preferably a polyalkyleneoxy structure having 2 to 15 carbon atoms, more preferably a polyalkyleneoxy structure having 3 to 10 carbon atoms), and It is preferable that the polyalkyleneoxy structure has at least one structure selected from the group consisting of a polyalkyleneoxy structure having 5 to 6 carbon atoms, and more preferable that the polyalkyleneoxy structure has at least one structure selected from the group consisting of a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure, it is preferable that the polyalkyleneoxy structure has at least one structure selected from the group consisting of a phenoxy structure, a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure, and it is more preferable that the polyalkyleneoxy structure has at least one structure selected from the group consisting of a phenoxy structure, a polybutadiene structure, a polyisoprene structure, and a polycarbonate structure.
[0033] The specific polymer preferably has a high molecular weight in order to exhibit flexibility. The number average molecular weight (Mn) of the specific polymer is preferably 1,000 or more and 1,000,000 or less, and more preferably 5,000 or more and 900,000 or less. The number average molecular weight (Mn) is a polystyrene-equivalent number average molecular weight measured using GPC (gel permeation chromatography).
[0034] The specific polymer is preferably selected from polymers having a glass transition temperature (Tg) of 25°C or lower and polymers that are liquid at 25°C in order to exhibit flexibility. The glass transition temperature (Tg) of the polymer having a glass transition temperature of 25° C. or lower is preferably 20° C. or lower, more preferably 15° C. or lower. There is no particular restriction on the lower limit of the glass transition temperature, and it can be appropriately selected depending on the purpose, but it is preferably −15° C. or higher. As the polymer that is liquid at 25°C, a polymer that is liquid at 20°C or less is preferable, and a polymer that is liquid at 15°C or less is more preferable.
[0035] From the viewpoint of improving the mechanical strength of the cured product, the specific polymer preferably has a functional group capable of reacting with the curing component. The functional group capable of reacting with the curing component also includes a functional group that appears upon heating. The functional group capable of reacting with the curing component is, for example, one or more functional groups selected from the group consisting of a hydroxy group, a carboxy group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, and a urethane group. Among these, the functional group is preferably a hydroxy group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, or a urethane group, and more preferably a hydroxy group, an acid anhydride group, a phenolic hydroxyl group, or an epoxy group.
[0036] The content of the specific polymer is preferably 1 vol.% or more and 50 vol.% or less, more preferably 1 vol.% or more and 30 vol.% or less, even more preferably 1 vol.% or more and 20 vol.% or less, and particularly preferably 1 vol.% or more and 10 vol.% or less, based on the total amount of the thermally conductive composition.
[0037] <Other ingredients> The thermally conductive composition may contain other components as long as the effects of the present invention are not impaired. The other components are not particularly limited and can be appropriately selected depending on the purpose. Examples of the other components include thermally conductive particles other than metals (e.g., aluminum nitride, alumina, carbon fibers, etc.), additives (e.g., antioxidants, ultraviolet absorbers, curing accelerators, silane coupling agents, leveling agents, flame retardants, etc.), and the like.
[0038] The thermally conductive composition can be prepared by uniformly mixing the curing component, the curing agent, and the metal filler, and, if necessary, the specific polymer and other components, by a conventional method.
[0039] The thermally conductive composition may be either a thermally conductive sheet in sheet form or a thermally conductive paste in paste form (also called a thermally conductive adhesive or a thermally conductive grease). Among these, a thermally conductive sheet is preferred from the viewpoint of ease of handling, and a thermally conductive paste is preferred from the viewpoint of cost.
[0040] (Method of manufacturing laminate) The method for producing a laminate of the present invention includes a first applying step and a heating step, and preferably includes a second applying step, and further includes other steps as necessary.
[0041] [Method for manufacturing the laminate of the first embodiment] In one embodiment, the method for manufacturing the laminate includes a first application step and a heating step, thereby making it possible to manufacture a laminate (a laminate of the first embodiment) having a base material and a first thermally conductive layer provided on the base material. As a result, a thermally conductive layer containing the curing component, the curing agent, and a sintered body formed by sintering the metal filler is formed on the base material, and the sintered body is connected in the thickness direction and planar direction of the thermally conductive layer, thereby making it possible to produce a laminate that can achieve high thermal conductivity and low thermal resistance.
[0042] [Method for manufacturing the laminate according to the second embodiment] In another embodiment, the method for manufacturing the laminate includes a first application step, a second application step, and a heating step, thereby making it possible to manufacture a laminate (a laminate of the second embodiment) having a base material, a first thermally conductive layer provided on the base material, and a second thermally conductive layer provided on the first thermally conductive layer. Thereby, by further comprising a second thermally conductive layer having a low melting point metal in comparison with the laminate of the first embodiment, a laminate capable of realizing an even higher heat dissipation effect (higher thermal conductivity) can be manufactured.
[0043] <First application step> The first application step is a step of applying the above-mentioned thermally conductive composition of the present invention (sometimes referred to as "first thermally conductive composition") onto the substrate. The curing component, curing agent, metal filler, and other components contained in the thermally conductive composition can be appropriately selected from those described in the thermally conductive composition of this embodiment.
[0044] Examples of methods for applying the first thermally conductive composition to the substrate include an inkjet method, a blade coating method, a gravure coating method, a gravure offset coating method, a bar coating method, a roll coating method, a knife coating method, an air knife coating method, a comma coating method, a U comma coating method, an AKKU coating method, a smoothing coating method, a microgravure coating method, a reverse roll coating method, a four-roll coating method, a five-roll coating method, a dip coating method, a curtain coating method, a slide coating method, and a die coating method. The first thermally conductive composition in a sheet form may be applied onto the substrate by means of transfer or the like.
[0045] -Base material- The shape, structure, size, material, etc. of the substrate are not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape of the substrate include a plate shape, a sheet shape, etc. Examples of the structure of the substrate include a single-layer structure, a laminated structure, etc. The size of the substrate can be appropriately selected depending on the application, etc.
[0046] As the material for the substrate, a material that is difficult for solder to wet can be selected because the first thermally conductive layer in contact with the substrate does not contain a low-melting point metal. Suitable examples of the material for the substrate include silicon, aluminum, tungsten, molybdenum, glass, molded resin, stainless steel, and ceramics. Examples of the ceramics include aluminum nitride, silicon carbide, alumina, and gallium nitride. Examples of the molding resin include epoxy resin, silicone resin, urethane resin, and acrylic resin. The substrate is preferably a silicon substrate. Furthermore, since the first thermally conductive layer has a sintered body formed by sintering the metal filler and communicating in the thickness direction and planar direction of the thermally conductive layer, in contact with the base material, a base material that does not have a metal plating layer can be suitably used as the base material, and a laminate that can achieve high thermal conductivity and low thermal resistance can be produced.
[0047] In addition, since the metal filler does not become completely fluidized in the first thermally conductive composition, the process of metallizing the substrate with gold in advance, which is generally required when sintering using silver microparticles, is not required. Compared to the general silver powder used to prepare the conventional silver sintered body, the metal filler does not melt and flow as a whole, and the sintered body formed by sintering the metal filler maintains a part of the particle shape while the metal filler is connected to each other, and becomes a sintered body that can efficiently conduct heat in the thickness direction and the planar direction of the thermal conductive layer. Therefore, the conventional silver powder and silver sintered body that melt and connect to the substrate having a metal plating layer and the metal filler and sintered body of this embodiment have different characteristics.
[0048] The average thickness of the substrate is not particularly limited and can be appropriately selected depending on the purpose. The substrate may be the heat generating body (electronic component) itself in the heat dissipation structure.
[0049] <Heating process> The heating step is a step of heating the thermally conductive composition, thereby forming a first thermally conductive layer on the substrate. In addition, when the method includes a second heating step described below, the heating step is a step of heating the first thermally conductive composition and the second thermally conductive composition, thereby forming a first thermally conductive layer and a second thermally conductive layer on the substrate.
[0050] The heating conditions are not particularly limited as long as the metal filler contained in the thermally conductive composition can be sintered to form the sintered body and the curing component and the curing agent can react with each other to cure, and can be appropriately selected depending on the purpose. For example, a temperature of 120°C to 190°C for 1 minute to 30 minutes is preferable, and a temperature of 140°C to 170°C for 1 minute to 10 minutes is more preferable.
[0051] <Second applying step> The second applying step is a step of applying a second thermally conductive composition onto the thermally conductive composition (first thermally conductive composition) applied onto the base material.
[0052] Examples of methods for applying the second thermally conductive composition to the substrate include an inkjet method, a blade coating method, a gravure coating method, a gravure offset coating method, a bar coating method, a roll coating method, a knife coating method, an air knife coating method, a comma coating method, a U comma coating method, an AKKU coating method, a smoothing coating method, a microgravure coating method, a reverse roll coating method, a four-roll coating method, a five-roll coating method, a dip coating method, a curtain coating method, a slide coating method, and a die coating method. The second thermally conductive composition in a sheet form may be applied onto the substrate by means of transfer or the like.
[0053] By applying the second thermally conductive composition onto the first thermally conductive composition in the liquid phase and then carrying out a heating step, the adhesiveness of the resulting first and second thermally conductive layers can be improved. In addition, the flux activity of the curing agent is expressed in the subsequent heating step, and the wettability between the molten low-melting point metal and the second thermally conductive particles can be improved.
[0054] -Second thermally conductive composition- The second thermally conductive composition contains a second curing component, a second curing agent, second thermally conductive particles, and low-melting point metal particles, and may further contain other components as required.
[0055] -Second hardening component- The second curing component preferably contains at least one of an oxetane compound and an epoxy resin, and more preferably contains an oxetane compound and an epoxy resin. The second curing component, the oxetane compound, and the epoxy resin can be appropriately selected from the items explained in the curing component of the thermoplastic resin of the present invention described above.
[0056] The content of the second curing component in the second thermally conductive composition is not particularly limited and may be appropriately selected depending on the purpose. The content is preferably 0.5 vol.% or more and 20 vol.% or less, and more preferably 1 vol.% or more and 15 vol.% or less, based on the total amount of the second thermally conductive composition.
[0057] -Second hardener- The curing agent is a curing agent corresponding to the curing component, and examples thereof include polyaddition type curing agents such as polyfunctional carboxylic acid, acid anhydride type curing agent, aliphatic amine type curing agent, aromatic amine type curing agent, phenol type curing agent, and mercaptan type curing agent, and catalyst type curing agents such as imidazole. These may be used alone or in combination of two or more. Among these, polyfunctional carboxylic acids are preferred, and glutaric acid is preferred. As the second curing agent, any of the items explained in relation to the curing agent for the thermoplastic resin of the present invention can be appropriately selected.
[0058] The content of the second curing agent in the second thermally conductive composition is not particularly limited and may be appropriately selected depending on the purpose. The content is preferably 0.5 vol.% or more and 20 vol.% or less, and more preferably 1 vol.% or more and 15 vol.% or less, based on the total amount of the second thermally conductive composition.
[0059] -Second thermally conductive particle- The second thermally conductive particles are preferably at least any one of copper particles, silver-coated particles, and silver particles, and more preferably silver-coated particles. Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles. The shape of the second thermally conductive particles is not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape include spherical, flat, granular, and acicular shapes.
[0060] The volume average particle diameter of the second thermally conductive particles is preferably 1 μm or more and 100 μm or less, more preferably 5 μm or more and 70 μm or less, and even more preferably 5 μm or more and 50 μm or less. When the volume average particle diameter of the second thermally conductive particles is 1 μm or more and 100 μm or less, excellent thermal conductivity can be achieved. The volume average particle size of the second thermally conductive particles can be measured in the same manner as the volume average particle size of the metal filler.
[0061] -Low melting point metal- The low melting point metal means the low melting point metal particles and the low melting point metal formed by melting and solidifying the low melting point metal particles. As the low melting point metal particles, solder particles as specified in JIS Z3282-1999 are preferably used.
[0062] Examples of the solder particles include Sn-Pb solder particles, Pb-Sn-Sb solder particles, Sn-Sb solder particles, Sn-Pb-Bi solder particles, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Cu solder particles, Sn-Pb-Cu solder particles, Sn-In solder particles, Sn-Ag solder particles, Sn-Pb-Ag solder particles, Pb-Ag solder particles, Sn-Ag-Cu solder particles, etc. These may be used alone or in combination of two or more. Among these, solder particles containing Sn and at least one selected from Bi, Ag, Cu, and In are preferred, Sn-Bi based solder particles, Sn-Bi-Ag based solder particles, Sn-Ag-Cu based solder particles, and Sn-In based solder particles are more preferred, and Sn-Bi based solder particles containing Sn and Bi are even more preferred.
[0063] The shape of the low melting point metal particles is not particularly limited and may be appropriately selected depending on the purpose. Examples of the shape include spherical, flat, granular, and acicular shapes. The melting point of the low-melting-point metal particles is preferably 100°C or higher and 250°C or lower, and more preferably 120°C or higher and 200°C or lower.
[0064] The melting point of the low-melting point metal particles is preferably lower than the heating temperature in the heating step. This allows the formation of a second thermally conductive layer in which a network (continuous metal phase) is formed by the molten low-melting-point metal via the second thermally conductive particles during the curing of the second thermally conductive composition, thus realizing a laminate with excellent heat resistance, thermal conductivity, and adhesiveness.
[0065] The volume average particle diameter of the low-melting metal particles is preferably 10 μm or less, more preferably 1 μm or more and 7 μm or less. When the volume average particle diameter of the low-melting metal particles is 10 μm or less, the volume ratio of the low-melting metal particles to the second thermal conductive particles can be reduced, and high thermal conductivity and low thermal resistance of the second thermal conductive layer can be achieved. The volume average particle size of the low-melting point metal particles can be measured in the same manner as the volume average particle size of the metal filler.
[0066] The volume average particle size of the second thermally conductive particles is larger than that of the low-melting-point metal particles, and the volume average particle size ratio (α / β) of the second thermally conductive particles α to the low-melting-point metal particles β is preferably 1.5 or more. The upper limit of the volume average particle size ratio (α / β) is preferably 10 or less. By using low-melting point metal particles having a smaller volume average particle size than the second thermally conductive particles, the second thermally conductive particles become the main component in the second thermally conductive composition, and the low-melting point metal particles present between the second thermally conductive particles and the second thermally conductive particles melt when heated and alloy with the second thermally conductive particles to form a network, thereby achieving high thermal conductivity and low thermal resistance.
[0067] In the second thermally conductive composition for forming the second thermally conductive layer, the volume ratio (α / β) of the second thermally conductive particles α to the low-melting point metal particles β is preferably at least 1, more preferably at least 1.5, and even more preferably at least 1.8. The upper limit of the volume ratio (α / β) is preferably at most 4, and more preferably at most 3.
[0068] <Other processes> The other steps are not particularly limited and may be appropriately selected depending on the purpose. For example, a protective layer forming step, an opposing substrate laminating step, and the like may be included.
[0069] (Laminate) The laminate of the present invention has a substrate and a first thermally conductive layer, and preferably further has a second thermally conductive layer, and may further have an opposing substrate and other members as necessary.
[0070] [Laminate of the first embodiment] In one embodiment, the laminate includes a substrate and a first thermally conductive layer provided on the substrate, the first thermally conductive layer including a curing component, a curing agent, and a sintered body. The sintered body is formed by sintering the metal filler, and is a sintered body that is continuous in the thickness direction and the planar direction of the first thermal conduction layer. The volume filling rate of the sintered body in the thermally conductive layer is 30 volume % or more and 90 volume % or less.
[0071] The laminate of the first embodiment can be suitably produced by the method for producing a laminate of the first embodiment. According to the laminate of the first embodiment, a thermally conductive layer containing the sintered body is formed on the base material, and the sintered body is interconnected in the thickness direction and the planar direction of the thermally conductive layer, thereby realizing high thermal conductivity and low thermal resistance. Specifically, the interconnected sintered body has a high heat dissipation effect, thereby realizing a thermal conductivity of 10 W / (m·K) or more, preferably a thermal conductivity of 15 W / (m·K) or more. In addition, zero contact thermal resistance can be realized even for a base material that does not have a metal plating layer.
[0072] [Laminate of the second embodiment] In another embodiment, the laminate includes a substrate, a first thermally conductive layer provided on the substrate, and a second thermally conductive layer provided on the first thermally conductive layer. The second thermally conductive layer contains a second hardening component, a second hardening agent, a second metal filler, and low-melting point metal particles, and may further contain other components as required.
[0073] The laminate of the second embodiment can be suitably produced by the method for producing a laminate of the second embodiment. The laminate of the second embodiment further includes a second thermally conductive layer having a low melting point metal, which makes it possible to realize a higher heat dissipation effect (higher thermal conductivity) than the laminate of the first embodiment. A thermal conductivity of 15 W / (m K) or more, preferably 20 W / (m K) or more can be realized.
[0074] <Base material> The substrate can be appropriately selected from the items explained in the above-mentioned method for producing a laminate of the present invention.
[0075] <First thermal conductive layer> The first thermally conductive layer is preferably formed on the base material and in contact with the base material. The first thermally conductive layer contains a hardening component, a hardener, and a sintered body. The curing component and the curing agent can be appropriately selected from those described above in relation to the thermally conductive composition of the present invention.
[0076] -Sintered body- The sintered body is formed by sintering the metal filler, and is a sintered body that is continuous in the thickness direction and the planar direction of the first thermal conduction layer. The sintered body is in contact with the base material, and as a result, the contact thermal resistance can be made zero even with a base material that does not have a metal plating layer, thereby achieving high thermal conductivity and low thermal resistance.
[0077] The volume filling rate of the sintered body in the heat conductive layer is 30 volume % or more and 90 volume % or less, and preferably 50 volume % or more and 80 volume % or less. The lower limit of the volumetric filling rate of the sintered body is 30% by volume or more, preferably 50% by volume or more, more preferably 60% by volume or more, even more preferably 70% by volume or more, and particularly preferably 75% by volume or more. The upper limit of the volumetric filling rate of the sintered body is 90% by volume or less, preferably 85% by volume or less, and more preferably 80% by volume or less. When the volume filling rate of the sintered body is 30 volume % or more and 90 volume % or less, the laminate can achieve high thermal conductivity and low thermal resistance.
[0078] The average thickness of the first thermally conductive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 10 μm to 300 μm, and more preferably from 20 μm to 200 μm.
[0079] <Second heat conductive layer> The second thermally conductive layer contains a second hardening component, a second hardening agent, a second metal filler, and low-melting point metal particles, and may further contain other components as required. The second curing component, the second curing agent, the second metal filler, and the low-melting point metal particles can be appropriately selected from those explained in the above-mentioned method for producing a laminate of the present invention.
[0080] The average thickness of the second thermally conductive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 20 μm to 300 μm, and more preferably from 50 μm to 200 μm.
[0081] <Facing substrate> The opposing substrate is disposed opposite the substrate, and its shape, structure, size, material, etc. are not particularly limited and can be appropriately selected depending on the purpose. The shape of the opposing substrate may be, for example, a plate shape, a sheet shape, etc. The structure of the opposing substrate may be, for example, a single-layer structure, a laminated structure, etc. The size of the opposing substrate may be appropriately selected depending on the application, etc. The material of the facing base material is a material that is easily wetted by solder, and includes at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof. The average thickness of the opposing substrate is not particularly limited and can be appropriately selected depending on the purpose. The opposing base material may be the heat spreader itself in the heat dissipation structure.
[0082] <Other materials> The other members are not particularly limited and can be appropriately selected depending on the purpose. For example, a protective layer can be mentioned.
[0083] Here, the laminate manufacturing method and the laminate according to the present invention will be described in detail with reference to the drawings. In each drawing, the same components are denoted by the same reference numerals, and duplicated descriptions may be omitted. In addition, the number, position, shape, etc. of the following components are not limited to the present embodiment, and may be any number, position, shape, etc. that is preferable for implementing the present invention.
[0084] FIG. 1 is a schematic diagram showing an example of a process for producing a laminate according to the first embodiment. The pre-cured laminate 10a shown in FIG. 1 is a laminate after the first application step and before the heating step, and specifically has a first thermally conductive composition 12a containing metal filler 12b on a substrate 11, and an opposing substrate 15 on the first thermally conductive composition 12a.
[0085] FIG. 2 is a schematic diagram showing an example of the laminate according to the first embodiment. The laminate 10 shown in FIG. 2 has a first thermally conductive layer 12 containing a sintered body 12c formed by sintering metal filler 12b on a substrate 11, and an opposing substrate 15 on the first thermally conductive layer 12.
[0086] FIG. 3 is a schematic diagram showing an example of a process of the method for producing a laminate according to the second embodiment. The pre-cured laminate 20a shown in FIG. 3 is a wet-on-wet pre-cured laminate after the first application step and the second application step and before the heating step, and specifically has a first thermally conductive composition 12a containing metal filler 12b on a substrate 11, a second thermally conductive composition 14a containing second thermally conductive particles 14b and low-melting point metal particles 14c on the first thermally conductive composition 12a, and an opposing substrate 15 on the second thermally conductive composition 14a.
[0087] FIG. 4 is a schematic diagram showing an example of a laminate according to the second embodiment. The laminate 20 shown in FIG. 4 has a first thermally conductive layer 12 containing a sintered body 12c formed by sintering metal filler 12b on a substrate 11, a second thermally conductive layer 14 containing second thermally conductive particles 14b and a low-melting point metal 14d on the first thermally conductive layer 12, and an opposing substrate 15 on the second thermally conductive layer 14.
[0088] The laminate of the present invention can be suitably used, for example, as a thermal interface material (TIM) that fills the minute gap between a heat source such as an LSI and a heat sink, thereby allowing heat to flow smoothly between the two, or when adhering a heat dissipation substrate mounting an LED chip or an IC chip to a heat sink to form a power LED module or a power IC module. Here, the power LED module is classified into a wire bonding mounting type and a flip chip mounting type, and the power IC module is classified into a wire bonding mounting type.
[0089] (heat dissipation structure) The heat dissipation structure of the present embodiment includes a heat generating body, the above-described laminate of the present invention, and a heat dissipation member, and further includes other members as necessary.
[0090] The heating element is not particularly limited and can be appropriately selected depending on the purpose. Examples of the heating element include electronic components such as a central processing unit (CPU), a micro processing unit (MPU), and a graphics processing unit (GPU).
[0091] The heat dissipation member is not particularly limited as long as it is a structure that dissipates heat generated by an electronic component (heat generating body), and can be appropriately selected depending on the purpose. Examples of the heat dissipation member include a heat spreader, a heat sink, a vapor chamber, and a heat pipe. The heat spreader is a member for efficiently transferring heat from the electronic component to other components. The material of the heat spreader is not particularly limited and can be appropriately selected depending on the purpose, and examples of the material include copper and aluminum. The heat spreader is usually in a flat plate shape. The heat sink is a member for releasing heat from the electronic component into the air. The material of the heat sink is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include copper and aluminum. The heat sink has, for example, a plurality of fins. The heat sink has, for example, a base portion and a plurality of fins provided so as to extend in a non-parallel direction (for example, a direction perpendicular to) one surface of the base portion. The heat spreader and the heat sink are generally solid structures with no internal voids. The vapor chamber is a hollow structure. A volatile liquid is sealed in the internal space of the hollow structure. Examples of the vapor chamber include a hollow structure of the heat spreader, a hollow plate-shaped structure of the heat sink, and the like. The heat pipe is a hollow structure having a cylindrical, approximately cylindrical, or flattened tubular shape, and a volatile liquid is sealed in the internal space of the hollow structure.
[0092] Here, Fig. 1 is a schematic cross-sectional view showing an example of a semiconductor device as a heat dissipation structure. The laminate 7 of the present invention dissipates heat generated by an electronic component 3 such as a semiconductor element, and is fixed to a main surface 2a of a heat spreader 2 facing the electronic component 3, as shown in Fig. 1, and is sandwiched between the electronic component 3 and the heat spreader 2. In addition, a thermally conductive sheet 1 is sandwiched between the heat spreader 2 and a heat sink 5.
[0093] The heat spreader 2 is formed, for example, in the shape of a rectangular plate, and has a main surface 2a facing the electronic component 3, and a side wall 2b erected along the outer periphery of the main surface 2a. The heat spreader 2 has a thermally conductive sheet 1 provided on the main surface 2a surrounded by the side wall 2b, and a heat sink 5 provided on the other surface 2c opposite the main surface 2a via the thermally conductive sheet 1. The higher the thermal conductivity of the heat spreader 2, the lower the thermal resistance and the more efficiently it absorbs heat from the electronic component 3 such as a semiconductor element, so the heat spreader 2 can be formed, for example, using copper or aluminum, which have good thermal conductivity.
[0094] The electronic component 3 is, for example, a semiconductor element such as a BGA, and is mounted on the wiring board 6. The tip surface of the side wall 2b of the heat spreader 2 is also mounted on the wiring board 6, so that the side wall 2b surrounds the electronic component 3 at a predetermined distance. By providing the laminate 7 of the present invention on the main surface 2a of the heat spreader 2, a heat dissipation member that absorbs heat generated by the electronic component 3 and dissipates the heat from the heat sink 5 is formed. EXAMPLES
[0095] Examples of the present invention will be described below, but the present invention is not limited to these examples.
[0096] (Example 1-1) <Preparation of Thermally Conductive Composition> The composition and contents shown in Table 1 were mixed uniformly using a stirring device (Awatori Rentaro Automatic Orbital Mixer, manufactured by Thinky Corporation) to prepare a first thermally conductive composition. The content of each component in Tables 1 to 7 is in volume percent.
[0097] <Production of Laminate> Next, a first thermally conductive composition was applied onto a substrate (silicon substrate) measuring 20 mm x 20 mm x 1 mm, and an opposing substrate (copper) measuring 20 mm x 20 mm x 1 mm was laminated onto the applied first thermally conductive composition. The laminate was pressed for 5 minutes in a mini press under conditions of an upper plate temperature on the copper substrate side of 150°C, a lower plate temperature on the silicon substrate side of 150°C, and a set air pressure of 0.11 MPa (40 psi in terms of pressure) to harden the composition, thereby producing the laminate of Example 1-1 having a first thermally conductive layer with an average thickness of 101 μm.
[0098] (Examples 1-2 to 1-9) Laminates of Examples 1-2 to 1-9 were produced in the same manner as in Example 1-1, except that the composition of the first thermally conductive composition in Example 1-1 was changed as shown in Tables 1 and 2.
[0099] (Comparative Examples 1-1 to 1-4) Laminates of Comparative Examples 1-1 to 1-4 were produced in the same manner as in Example 1-1, except that the composition of the first thermally conductive composition in Example 1-1 was changed as shown in Table 3.
[0100] Next, for each of the obtained laminates, "measurement of the average thickness of each layer" and "thermal conductivity" were evaluated as follows. The results are shown in Tables 1 to 3.
[0101] <Measurement of the average thickness of each layer> Each laminate was cut, the cut surface was polished, and the polished surface was photographed with a scanning electron microscope (S-3000N, manufactured by Hitachi, Ltd.). The thickness of each layer was measured from the cut surface of the laminate, and the average value of the thicknesses at three arbitrary points was calculated. The results are shown in Tables 1 to 3. It was confirmed that each of the laminates of the Examples had a first thermally conductive layer and an opposing substrate in this order on a substrate, corresponding to the cross-sectional view of the laminate shown in FIG.
[0102] <Thermal conductivity> <<Preparation of laminated body after compression>> Each laminate was sandwiched between a 20 mm x 20 mm square silicon plate (thickness 0.77 mm) and a 20 mm diameter copper plate (thickness 1.0 mm) and pressed for 5 minutes using a mini press under the following conditions: upper plate temperature on the copper substrate side was 150°C, lower plate temperature on the silicon substrate side was 150°C, and set air pressure was 0.11 MPa (40 psi in terms of pressure).
[0103] <<Evaluation of thermal conductivity>> After bonding, the thermal resistance (℃ cm) of the laminate (interface Cu and silicon) was measured using a method in accordance with ASTM-D5470. 2 The thermal resistance of the laminate was calculated by subtracting the thermal resistance of the substrate (silicon substrate) and the opposing substrate (copper substrate) from the results, and the thermal resistance of the portion excluding the substrate and the opposing substrate from the laminate was calculated. The thermal conductivity (W / m K) was calculated from this thermal resistance and the thickness (100 μm) of the portion excluding the substrate and the opposing substrate from the laminate, and the thermal conductivity was evaluated according to the following criteria. [Evaluation Criteria] ◎: Thermal conductivity is 20 W / m K or higher. Good: Thermal conductivity is 10 W / m K or more and less than 20 W / m K. ×: Thermal conductivity is less than 10 W / m K.
[0104] [Table 1]
[0105] [Table 2]
[0106] [Table 3]
[0107] (Example 2-1) <Preparation of Thermally Conductive Composition> The compositions and contents shown in Table 4 were mixed uniformly using a stirring device (Awatori Rentaro Automatic Orbital Mixer, manufactured by Thinky Corporation) to prepare a first thermally conductive composition and a second thermally conductive composition.
[0108] <Production of Laminate> A first thermally conductive composition having an average thickness of 30 μm and a second thermally conductive composition having an average thickness of 70 μm were laminated at 75° C. to obtain a thermally conductive composition having a two-layer structure. The surface with the first thermally conductive layer was applied onto a 20 mm x 20 mm x 1 mm substrate (silicon substrate), and a 20 mm x 20 mm x 1 mm opposing substrate (copper) was laminated onto the second thermally conductive composition. The laminate was then pressed for 5 minutes in a mini press under conditions of an upper plate temperature of 150°C on the copper substrate side, a lower plate temperature of 150°C on the silicon substrate side, and a set air pressure of 0.11 MPa (40 psi in terms of pressure) to harden the laminate, forming Example 2-1 having a first thermally conductive layer and a second thermally conductive layer and a total average thickness of 99 μm.
[0109] (Examples 2-2 to 2-9) Laminates of Examples 2-2 to 2-9 were produced in the same manner as in Example 2-1, except that the composition of the first thermally conductive composition in Example 2-1 was changed as shown in Tables 4 to 5.
[0110] (Comparative Examples 2-1 to 2-3) Laminates of Comparative Examples 2-1 to 2-3 were produced in the same manner as in Example 1-1, except that in Example 2-1, the composition of the first thermally conductive composition was changed as shown in Table 6.
[0111] Next, for each of the obtained laminates, "the average thickness of each layer" and "thermal conductivity" were measured. The results are shown in Tables 4 to 6.
[0112] [Table 4]
[0113] [Table 5]
[0114] [Table 6]
[0115] (Examples 3-1 to 3-2) Except for changing the combination of the substrate and the opposing substrate in Example 1-1 as shown in Table 7, laminates of Examples 3-1 and 3-2 were produced in the same manner as in Example 1-1. It was confirmed that the thermal conductivity did not change regardless of the type of the substrate and the opposing substrate. From this result, it was found that the contact thermal resistance reached zero.
[0116] (Example 3-3) Except for changing the thickness of the first thermally conductive layer in Example 1-1 as shown in Table 7, laminates of Examples 3-1 to 3-3 were produced in the same manner as in Example 1-1. It was confirmed that the thermal conductivity did not change regardless of the thickness of the first thermally conductive layer, and this result showed that the contact thermal resistance reached zero.
[0117] (Examples 3-4) Laminates of Examples 3-4 were produced in the same manner as in Example 2-1, except that the combinations of the substrate and the opposing substrate in Example 2-1 were changed as shown in Table 7. It was confirmed that the thermal conductivity did not change regardless of the type of the substrate and the opposing substrate. From this result, it was found that the contact thermal resistance reached zero.
[0118] [Table 7]
[0119] Details of each component in Tables 1 to 7 are as follows.
[0120] -Curing component A- Epoxy resin: EPICLON (registered trademark) EXA-850CRP (DIC Corporation)
[0121] - Hardener B - Epoxy resin hardener: Curesol (registered trademark) 2P4MZ (manufactured by Shikoku Chemical Industries Co., Ltd.)
[0122] -Metal filler C- Ag particles (D50: 1 μm): Ag particles, manufactured by DOWA Electronics Co., Ltd., volume average particle size Dv: 1 μm Ag particles (D50: 2 μm): Ag particles, manufactured by DOWA Electronics Co., Ltd., volume average particle size Dv: 2 μm Ag-coated Cu particles (D50: 5 μm): Ag-coated Cu particles, manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size Dv: 5 μm Cu particles (D50: 5 μm): Manufactured by Fukuda Metal Foil and Powder Co., Ltd., Volume average particle size Dv: 5 μm The volume average particle size Dv of the metal filler is a value measured by a laser diffraction / scattering type particle size distribution measuring device (product name: Microtrac MT3300EXII).
[0123] -Polymer D- YP-50 (manufactured by Nippon Steel Chemical & Material Co., Ltd.), a polyhydroxypolyether synthesized from bisphenols and epichlorohydrin
[0124] -Curing component- Curing component (oxetane compound): ETERNACOLL (registered trademark) OXBP (manufactured by Ube Industries, Ltd.), 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl
[0125] - Hardener - Glutaric acid: 1,3-propanedicarboxylic acid, manufactured by Tokyo Chemical Industry Co., Ltd.
[0126] -Low melting point metal particles (solder particles)- Sn 58 Bi 42Manufactured by Mitsui Mining & Smelting Co., Ltd., Volume average particle size Dv: 6μm, Melting point 139℃ The volume average particle size Dv of the low-melting point metal particles is a value measured by a laser diffraction / scattering type particle size distribution measuring device (product name: Microtrac MT3300EXII).
[0127] -Thermal conductive particles- Ag-coated Cu particles (Dv: 10 μm): Ag-coated Cu particles, manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size Dv: 10 μm [Industrial Applicability]
[0128] The laminate of the present invention can achieve excellent heat resistance, thermal conductivity, and adhesion as a thermal interface material (TIM), and is therefore suitable for use in, for example, the vicinity of various electric devices such as CPUs, MPUs, power transistors, LEDs, and laser diodes, whose element operation efficiency, life span, and the like are adversely affected by temperature. [Explanation of symbols]
[0129] 1. Thermal conductive sheet 2 Heat spreader 2a Main surface 3 Heating elements (electronic components) 3a Top side 5. Heat sink 6 Wiring board 7 Laminate 10 Laminate 10a Laminate before curing 11 Base material 12 First heat conductive layer 12a First thermally conductive composition 12b Metal filler 12c Sintered body 14 Second heat conducting layer 14a Second thermally conductive composition 14b Second thermally conductive particles 14c Low melting point metal particles 14d Low melting point metals 15 Opposing substrate
Claims
1. A substrate; A first thermally conductive layer provided on the base material, the first thermally conductive layer including a curing component, a curing agent, and a sintered body; the sintered body is formed by sintering at least one metal filler selected from silver particles, copper particles, silver-coated copper particles, and copper-coated silver particles, and is a sintered body that is continuous in a thickness direction and a planar direction of the first thermal conductive layer, A laminate, characterized in that a volume filling rate of the sintered body in the first thermally conductive layer is 30 volume % or more and 90 volume % or less.
2. 2. The laminate of claim 1, further comprising a second thermally conductive layer disposed on the first thermally conductive layer, the second thermally conductive layer comprising a second curing component, a second curing agent, a second metal filler, and low melting point metal particles.
3. The laminate according to claim 1 , wherein the substrate is a silicon substrate.
4. 3. The laminate according to claim 1, having a thermal conductivity of 10 W / (m·K) or more.
Citation Information
Patent Citations
Detector for defect of sheet-like substance
JP1982096242A